Adaptive changes of coral Galaxea fascicularis holobiont in response to nearshore stress - Zhu, Wentao; Zhu, Ming; Liu, Xiangbo; Xia, Jingquan; Wang, Hao; Chen, Rouwen; Li, Xiubao (Frontiers in Microbiology, 2022)
Global change and locally stressors are simultaneously affecting the nearshore corals, and microbiome flexibility may assist corals in thriving in such multiple stressors. Here, we investigated the effects of various pressure sources on Galaxea fascicularis holobiont from nearshore and offshore reefs. These nearshore reefs were more turbid, eutrophic, and warm than offshore reefs. However, coral physiological parameters did not differ significantly. Corals under stressful nearshore reduced the symbiont diversity and selected more tolerant Symbiodiniaceae. Bacterial diversity of offshore corals was significantly higher, and community composition varied obviously. Diffusion limitations and environmental heterogeneity were essential in structuring microbial communities. Functional annotation analysis demonstrated significant differences in bacterial functional groups between nearshore and offshore corals. Environmental stress significantly reduced the complexity, connectivity, and stability of bacterial networks, and the abundances of keystone taxa altered considerably. These results indicated that corals could thrive nearshore through holobiont plasticity to cope with multiple environmental stresses.